Pentingnya Pembelajaran Dalam Mengembangkan Kemampuan Bahasa Pada Anak Sekolah Dasar - Delva Sridayanti (Prodi PGSD Unsultra, 2023)
Speaking ability is an essential skill that students, especially in elementary schools, need to develop. One effective method to improve speaking skills is through classroom discussions. This article examines the role of classroom discussions in enhancing elementary school students' speaking skills based on various literature studies. Classroom discussions help students actively practice speaking, expand vocabulary, build self-confidence, and foster social skills development. The research shows that classroom discussions have a significant positive impact on students' speaking ability and should be implemented more frequently in elementary school learning activities.